(untitled) (Indian Journal of Nematology, 2024)
Aqueous extracts of leaves of botanicals i.e. Argemone maxicana, Azadirachta indica, Calotropis procera, Datura inoxia, Delonix regia, Parthenium hysterophorous, Moringa oteifera, Saraca asoka and Withania sominifera plants were tested against root-knot nematode, Meloidogyne incognita under in-vitro trials. Undiluted crude leaf extracts of A. maxicana, A. indica and P. hysterophorous exhibited 78, 62 and 70 larve inhibition from eggs and 100, 100 and 60% mortality (out of hatched juveniles), respectively whereas Purpureocillium lilacinum (check) exhibited 79% inhibition of egg hatch and 31% mortality. Another in-vitro trial on mortality of tested nematode was observed up to 72 h with a revival test for 24 h. After revival 100% mortality was recorded with A. indica followed by A. maxicana (90%) and P. hysterophorous (56%) whereas P. lilacinum killed only 38% M. incognita larvae. Under in-vivo test, leaf extracts of individual plants significantly (P>0.5) improved the growth of okra plants in presence of tested nematode and/or fungal bio-agent when compared to control. Maximum suppression of M. incognita in terms of number of galls 91 and 85% was achieved through application of A. maxicana and C. procera, respectively in presence of P. lilacinum followed by A. indica treatment (83%). It is noted in the present study that A. maxicana showed better nematicidal properties in presence of P. lilacinum in reducing nematode population in soil (81%) which is readily available to farmers as weed at no additional cost.